The Paris Agreement and Climate Justice: Inequitable Impacts of Sea Level Rise Associated With Temperature Targets. Issue 12 (12th December 2022) - Sadai, S.; Spector, R. A.; DeConto, R.; Gomez, N.
Abstract: Anthropogenic greenhouse gas emissions are causing unprecedented changes to the climate. In 2015, at the United Nations (UN) Conference of the Parties in Paris, France, countries agreed to limit the global mean temperature (GMT) increase to 2°C above preindustrial levels, and to pursue efforts to limit warming to 1.5°C. Due to the long‐term irreversibility of sea level rise (SLR), risks to island and coastal populations are not well encapsulated by the goal of limiting GMT warming by 2100. This review article investigates the climate justice implications of temperature targets in light of our increasing understanding of the spatially variable impact and long temporal commitment to rising seas. In particular we highlight the impact that SLR will have on island states and the role of the Alliance of Small Island States (AOSIS) in UN climate negotiations. As a case study we review dual impacts from the Antarctic Ice Sheet under a changing climate: (a) recent climate and ice sheet modeling shows that Antarctic melt has the potential to cause rapid SLR with a distinct spatial pattern leading to AOSIS nations experiencing SLR at least 11% higher than the global average and up to 33% higher; and (b) future ice sheet melt will result in a negative feedback on GMT, thus delaying temperature rise. When considering these impacts in conjunction, justice concerns associated with the Paris Agreement are exacerbated. Plain Language Summary: At the Paris Climate Agreement in 2015, countries adopted a target for stabilizing climate change defined by how the rise in global average air temperature has increased relative to a pre‐industrial baseline (1850–1900). Prior research has identified numerous climate justice implications associated with this approach. This study reviews climate justice issues associated with Paris Agreement temperature targets, finding that using air temperature by 2100 as the main metric does not adequately capture other climate risks, particularly sea level rise (SLR) faced by island and coastal communities. We introduce a new climate justice consideration based on the simultaneous impacts of SLR and slowed warming caused by ice loss on Antarctica. Slowed warming might appear to delay the need for climate action, but a focus on end‐of‐century temperature misses the impacts of long‐term accelerating SLR. Key Points: This review considers the Paris Agreement temperature target in the context of long‐term, spatially variable sea level rise We interpret reviewed literature through theories of climate justice, assessing impact to members of the Alliance of Small Island States Modeling of Antarctic melt indicates sea levels rise while temperature increase slows, complicating use of temperature targets post‐2100